Stadt-Umland-Wanderung in Nordrhein-Westfalen — Eine Meta-Analyse - Bleck, Markus; Wagner, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
Although research on city-hinterland-migration has been conducted in North-Rhine-Westphalia for almost four decades, only insufficient comparisons of the findings for different cities and years are available. Using meta-analysis, this paper summarizes and compares the existing studies in terms of year of data collection, research method etc. as well as characteristics of individual cities, such as density and population size. The results of this study contribute to a better understanding of city-hinterland-migration and a methodical improvement of future surveys about migration motives.